CerealESTDb: A Comprehensive Resource for Abiotic Stress-Responsive Annotated ESTs With Predicted Genes, Gene Ontology, and Metabolic Pathways in Major Cereal Crops - Kumar, Sanjeev; Bhati, Jyotika; Saha, Arijit; Lal, Shashi Bhushan; Pandey, Pankaj Kumar; Mishra, Dwijesh Chandra; Farooqi, Mohammad Samir; Kumar, Anuj; Chaturvedi, Krishna Kumar; Rai, Anil (Frontiers in Genetics, 2022)
Cereals are the most important food crops and considered as key contributors to global food security. The loss due to occurrence of abiotic stresses in cereal crops is limiting potential productivity in a significant manner. The primary reasons for abiotic stresses are abrupt temperature, variable rainfall and declining nutrient status of soil. Varietal development is the key to sustain productivity under influence of multiple abiotic stresses and need to study in context with genomics and molecular breeding. Recently, advances in a plethora of Next Generation Sequencing (NGS) based methods have accelerated the enormous genomic data generation associated with stress induced transcripts such as microarray, RNAseq, Expressed Sequenced Tag (ESTs) etc. Many databases related to microarray and RNA-seq based transcripts have been developed and profusely utilized. Though, abundant amount of transcripts related to abiotic stresses in various cereal crops arising from EST technology are available but still remains underutilized in absence of a consolidated database. In this study, an attempt has been made with a primary goal to integrate, analyse and characterise the available resources of ESTs responsive to abiotic stresses in major cereals. The developed CerealESTdb present a customizable search in two different ways in the form of searchable content for an easy access and potential use. This database comprises with ESTs from four major cereal crops namely, rice (Oryza sativa L.), wheat (Triticum aestivum L.), sorghum (Sorghum bicolour L.), and maize (Zea mays L.), under a set of abiotic stresses. The current statistics of this cohesive database consists of 55,826 assembled EST sequences, 51,791 predicted genes models and their 254,609 gene ontology terms including extensive information on 1,746 associated metabolic pathways. We anticipate that developed CerealESTdb will be helpful in deciphering the knowledge of complex biological phenomena under abiotic stresses to accelerate the molecular breeding programs towards development of crop cultivars resilient to abiotic stresses. The CerealESTdb is publically available with URL http://cabgrid.res.in/CerealESTDb.